Virus and virus-like particles observed in the intestinal contents of the possum,Trichosurus vulpecula - Rice, M. (Arch Virol, 1996)
Intestinal contents derived from the Australian brush-tailed possum,Trichosurus vulpecula, were examined by negative stain electron microscopy for the presence of viruses. Out of 100 samples, 23 contained at least one type of vertebrate virus or virus-like particle. Adenovirus was identified in six samples, herpesvirus in two samples, coronavirus in four samples, and coronavirus-like particles in 14 samples. To date no viruses of the brush-tailed possum have been isolated in tissue culture but these results indicate that this species is probably host to several viral species.